Bezpieczeństwo informacyjne w jednostkach samorządu terytorialnego: brak - Gerwatowski, Jacek (Studia Prawnoustrojowe, 2019)
This article analyses issues in the feld of information and IT security and attempts to explain what is meant by information security and presents potential opportunities and threats in this feld. The article discusses various types of information security threats, from those with a “traditional” character, such as espionage, through to threats resulting from the development of new technologies, e.g. cyber-terrorism and threats resulting from the activities of natural forces. The article presents the tasks of public administration and local government units in the feld of information security resulting, inter alia, from the provisions of the Act on access to public information or regulations on the protection of personal data. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">